UTILIZING EXAMPLES OF FOLK PEDAGOGY IN CHILD-REARING - Abdaliyeva, Peruza Isaevna (SCIENCE and SOCIETY, 2026)
The article deals with the problems of educating children by comprehensively developed people using samples of Karakalpak folk pedagogy in family education.